A thermoresponsive CA-PNIPAM-based electrospun nanofibrous membrane for oil/water separation. (26th September 2022) - Chauhan, Divya; Singh, Neha; Afreen, Shagufta; Talreja, Neetu; Ashfaq, Mohammad; Sankararamakrishnan, Nalini; Chaudhary, Ganga Ram
Abstract : The prepared electrospun CA-P fibrous membrane/mat has the potential ability for high-efficiency oil/water separation. Abstract : Oil released into the environment has become one of the foremost concerns that rigorously impact the environmental system. Therefore, there is a need to develop newer membranes, modify existing membranes, or tune the wettability of membranes. The present study focuses on the synthesis of thermo-responsive polymeric membranes based on cellulose acetate (CA) and poly( N -isopropyl acrylamide) (PNIPAM) (CA-P) produced by the electrospinning process for oil/water separation. The hydrophilicity/hydrophobicity is easily tuned by increasing the amount of PNIPAM in the electrospun CA-P fibrous membrane/mat. The electrospun CA-P fibrous membrane/mat possesses switchability in terms of hydrophilicity/hydrophobicity with increasing temperature. A higher contact angle of 122° at 50 °C was observed for the CA-P fibrous membrane/mat (1:3), indicating that a higher amount of PNIPAM loaded electrospun CA-P fibrous membrane/mat has higher hydrophobicity. The electrospun CA-P fibrous membrane/mat shows high hydrophilicity at room temperature and high hydrophobicity at higher temperatures, attributed to the switchable ability of the prepared electrospun CA-P fibrous membrane/mat. Therefore, the prepared electrospun CA-P fibrous membrane/mat has the potential ability for high-efficiency oil/water separation.